2017
DOI: 10.1051/0004-6361/201731497
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between symbiotic stars and planetary nebulae

Abstract: Context. Number of known symbiotic stars (SySt) is still significantly lower than their predicted population. One of the main problems in finding complete population of SySt is the fact that their spectrum can be confused with other objects, such as planetary nebulae (PNe) or dense H ii regions. The problem is reinforced by a fact that in significant fraction of established SySt the emission lines used to distinguish them from other objects are not present. Aims. We aim at finding new diagnostic diagrams that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Recently, Akras et al (2019b) proposed a set of IR criteria for classifying the symbiotic stars based on the IR photometry from 2MASS and WISE. Iłkiewicz & Mikołajewska (2017) presented spectroscopic criteria based on the ratio of emission line fluxes to distinguish between planetary nebulae and symbiotic stars, extending the diagnostic diagrams of Gutierrez-Moreno et al (1995) which are applicable only if [O ] emission lines are observed together with Balmer lines. In our recent work (Merc et al 2020), we have proposed to employ the position in the Gaia DR2 HR diagram, or the unusual X-ray-to-optical flux ratios as criteria to discard disputable symbiotic candidates and, to a lesser extent, to identify promising systems.…”
Section: Classification Criteriamentioning
confidence: 99%
“…Recently, Akras et al (2019b) proposed a set of IR criteria for classifying the symbiotic stars based on the IR photometry from 2MASS and WISE. Iłkiewicz & Mikołajewska (2017) presented spectroscopic criteria based on the ratio of emission line fluxes to distinguish between planetary nebulae and symbiotic stars, extending the diagnostic diagrams of Gutierrez-Moreno et al (1995) which are applicable only if [O ] emission lines are observed together with Balmer lines. In our recent work (Merc et al 2020), we have proposed to employ the position in the Gaia DR2 HR diagram, or the unusual X-ray-to-optical flux ratios as criteria to discard disputable symbiotic candidates and, to a lesser extent, to identify promising systems.…”
Section: Classification Criteriamentioning
confidence: 99%
“…planetary nebulae, Be stars and young stellar objects (e.g. Gutierrez-Moreno et al 1995;Rodríguez-Flores et al 2014;Iłkiewicz & Mikołajewska 2017). We have investigated how our emission models of symbiotic binaries fit to these previously presented line ratio classification diagrams and how the line ratios depend on the massloss rate and orbital separation.…”
Section: Line Ratiosmentioning
confidence: 99%
“…Gutierrez-Moreno et al (1995) used the [O ] and Balmer emission lines for the classification, but this method is not always applicable, because the [O ] are not always detected. Iłkiewicz & Mikołajewska (2017) explored various other emission lines including [N ], [O ], [Ne ], and He lines, in order to distinguish planetary nebulae from symbiotic binaries. They demonstrated that this set of lines provides an efficient diagnostics for symbiotic binaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SySts are further classified as S-type, for those where the mass donor is a normal giant star, and D-type, for systems where the donor is a Mira variable surrounded by a warm dust envelope (Webster & Allen 1975). SySts are use-shown that D-type SySts can, in fact, be distinguished from PNe by the strength of forbidden lines (O III and N III) and various He I lines in the optical region of the spectrum (Gutierrez-Moreno et al 1995;I lkiewicz & Miko lajewska 2017). Meanwhile, S-type SySts are typically identified by the presence of photospheric absorption features (TiO, VO, C 2 , CN) in the observed spectrum of the cool companion, in addition to presence of strong emission lines from He II and Hα, as well as from high-excitation ions (Fe VII, O VI; e.g., Belczyński et al 2000).…”
Section: Introductionmentioning
confidence: 99%